Formulation And Optimization Of Lipid-Polymer Hybrid Nanoparticles For Targeted Delivery Of Docetaxel: A Novel Approach In Cancer Therapy - Kaushik, Kunal; Kaushik, Dinesh (Journal of Neonatal Surgery, 2025)
Docetaxel, a potent chemotherapeutic agent, is widely used for the treatment of solid tumors such as breast, prostate, and lung cancer. However, its clinical use is limited by poor aqueous solubility, systemic toxicity, and multidrug resistance. The current study aimed to formulate and optimize lipid-polymer hybrid nanoparticles (LPHNs) of Docetaxel for improved tumor targeting, enhanced bioavailability, and reduced systemic side effects. LPHNs were prepared using the nanoprecipitation method combining PLGA (poly(lactic-co-glycolic acid)) as the polymeric core and lecithin/cholesterol as the lipid shell. A Box-Behnken design was employed to optimize the formulation parameters including lipid-to-polymer ratio, drug loading, and surfactant concentration. The optimized formulation exhibited a particle size of 145.3 ± 4.5 nm, PDI of 0.174, zeta potential of -22.6 ± 1.3 mV, and encapsulation efficiency of 89.6 ± 2.1%. In vitro drug release studies revealed a biphasic release profile with sustained release over 72 hours. Cytotoxicity studies on MCF-7 (breast cancer) cells showed significantly higher anticancer activity for LPHNs compared to free drug. These findings indicate that Docetaxel-loaded LPHNs offer a promising nanocarrier system for targeted cancer therapy